Genetic Diversity of Porang Populations (Amorphophallus Muelleri Blume) In Central Java and West Java Based on LEAFY Second Intron Marker - Nikmah, Isna Arofatun; Azrianingsih, Rodiyati; Wahyudi, Didik (Journal of Tropical Life Science, 2016)
Porang (Amorphophallus muelleri Blume) dispersed and grows well in Java island. This research aimed to determine the genetic diversity of porang populations in Central Java and West Java based on LEAFY second intron (nuclear genome encoding flower development). DNA samples of porang were from previous study, which are obtained from Central Java (Pamedaran, Grobogan, Wonogiri, Karangtengah) and West Java (Cisompet) as ingroup. A. variabilis from Pamedaran Brebes, A. ochroleucus, A. longituberosus, A. sumawongii, and A. tinekeae from genbank were treated as outgroup. LEAFY second intron was amplified using primers FLint2 F1 5’-CTTCCACCTCTACGACCAGTG-3’ and FLint2 R1 5’-TCTTGGGCTTGTTGATGTAGC-3’. Analysis using dnasp5 showed that 23 samples had 89 invariable sites and 139 variable sites that consisted of 12 singleton two variants sites, 118 parsimony-informative two variants sites and 9 Parsimony-informative three variants sites. The total of haplotype were 7 haplotypes where 16 ingroup samples clumped on haplotype 1 whereas 2 samples of Grobogan (Grobogan I and Grobogan III) clumped on haplotype 2 and outgroup samples occupied at their own haplotype. Genetic distance of all ingroup samples were 0-0,004 showing no differences among individuals. Analysis of phylogenetic tree using Maximum Parsimony, Neighbor Joining and Maximum Likelihood resulting a polytomy branch of ingroup samples except Grobogan which forms a separated sub clad. Key words: Genetic diversity, haplotype, Java, LEAFY, Porang.